Modeling the carbon consequences of pro-environmental consumer behavior. (15th December 2016) - Duarte, Rosa; Feng, Kuishuang; Hubacek, Klaus; Sánchez-Chóliz, Julio; Sarasa, Cristina; Sun, Laixiang
Highlights: Environmental and socio-economic implications of household lifestyle are studied. We explore the potential of different policies to achieve environmental outcomes. Achieving double dividends (economic and environmental goals) is possible. Results highlight the existence of "rebound effects". Inequalities in environmental pressures are observed. Abstract: Households, as consumers of goods and services through their lifestyles and spending choices, drive environmental change. Using a recent (2008) social and environmental survey of Spanish households, we evaluate the effects of improvements in environmental awareness, and of changes induced by regulations and carbon taxes. We consider these drivers of behavioral change for different income levels. A range of scenarios including the adoption of energy efficient appliances, modal shift to public transport, healthier diets, and the associated carbon emissions and job effects, are estimated using a Computable General Equilibrium (CGE) model. Our results suggest that reductions in carbon dioxide, methane, and sulphur dioxide emissions may be compatible with increases in income and reductions in unemployment. Modal shift to public transport is shown as a successful economic and environmental policy.